The effects of green finance on the carbon decoupling of marine fishery: analysis based on Tapio method and EKC model - Xu, Weicheng; Zhu, Yiying (Frontiers in Environmental Science, 2024)
Marine fishery, with its duality of carbon emission and carbon sink, is an industry that needs full attention during achieving carbon neutrality. In this paper, the decoupling index between net CO2 emissions and gross domestic product of marine fishery in China is calculated using Tapio model, and its evolution characteristics are analyzed by means of nuclear density map and Markov matrix. Some problems are found, such as the decoupling state lacked significant improvement during this period and was unstable. Through theoretical analysis, this paper puts forward the view that solving these problems requires support from green finance. Then, this paper selects panel data from 11 coastal provinces and cities in China from 2010 to 2020 and uses the Logit model and EKC model to investigate the impact of green finance on the carbon decoupling state of marine fishery. The main results of this study are as follows: 1) Green finance can increase the odds ratio of strong or weak decoupling in marine fishery. This effect is more significant in regions with a high degree of digital finance development and the eastern marine economic circle. The effect of green investment is more significant than green insurance. In addition, boosting technological innovation and reducing the proportion of coal consumption can strengthen this effect. 2) The EKC curve between net CO2 emissions and gross domestic product of marine fishery is N-shape, which has a deterioration point. Green finance can delay the arrival of the deterioration point, meaning it can prevent the rapid deterioration of the decoupling state with the development of marine fishery. This paper provides empirical evidence and decision-making reference for resolving the dilemma of carbon decoupling in China’s marine fishery.